Virtual presidency: an analysis of the political speech by Jair Bolsonaro on twitter - Barbosa, Laíse Milena (2022)
This article analyzes the political speech of Jair Bolsonaro in his Twitter profiles from August 2018 to December 2019. The objective is to verify if the publications coming from the website can be configured as hate speech, therefore, a qualitative and interpretive research. For that, Patrick Charadeau's fundamentals regarding the investigation of political discourse were used and some characteristics of the Twitter tool were exposed as an arena for debates. Also, the paradigmatic elements and cases that compose the debate on hate speech were identified in terms recognized by Political Science. Finally, based on these elements, we analyzed all posts within the selected profile Twitter Jair Bolsonaro through the deductive method and the documentary research technique focusing on critical discourse analysis. As a result, Bolsonaro's publications are part of a political discourse that composes a hate speech as it generates disbelief in the democratic order and human rights.